ANALISIS FAKTOR RISIKO TERHADAP KEJADIAN NON HEMORAGIC STROKE (NHS) DI RUANG PERAWATAN RSUP Dr. WAHIDIN SUDIROHUSODO MAKASSAR - Rosdewi, NFN; Wattimena, Christy (Jurnal Keperawatan Florence Nightingale, 2019)
Stroke problems are important things to pay attention. One type of Stroke that is often occurring by the public is a Non Hemorrhagic Stroke (NHS). Some of the risk factors at the root of the NHS are activism, smoking and alcohol consumption, hypertension, heart disease, diabetes mellitus, hypercholesterolemia, obesity, age and gender. This study aimed to compare risk factors with the incidence of Non Hemorrhagic Stroke (NHS) in Dr. Wahidin Sudirohusodo Makassar. The research design was an observational analytics with case control study approach. Sampling used a nonprobability sampling technique through consecutive sampling method with a sample size of 20 respondents. Data Collection was done by using secondary data that were from patient status book. The data were processed using SPSS for windows version 20.0 and analyzed with statistical test Odds Ratio. The results showed that the variables have an effect on the occurrence of recurrent NHS were blood pressure (p = 0.020, OR 21), Diabetes Mellitus (p = 0.023, OR 16). While the variables that have no effect on the occurrence of recurrent NHS was dyslipidemia (p = 1, OR 1). In multivariate analysis, it was found that blood pressure and Diabetes Mellitus had the same value (p = 0.998; OR 0.000) so it showed that blood pressure and Diabetes Mellitus were the most influential on recurrent NHS incidence. It is hoped that people will be more concerned about health by reducing the consumption of fatty foods, stopping smoking and consuming alcohol, often exercising and following treatment.